Better a Hundred Friends than a Hundred Rubles? Social Networks in Transition--The Kyrgyz Republic - Kuehnast, Kathleen; Dudwick, Nora (Washington, DC: World Bank, 2013)
The purpose of this study, carried out in the Kyrgyz Republic in 1999, was to investigate the impact of socioeconomic change on the characteristics and functions of the social networks of poor and non-poor households in rural and urban communities. A better understanding of the role of informal networks in Kyrgyz society, it was thought, would help development specialists devise more effective ways to reach out to the poor and socially excluded, while ensuring that the benefits of development were not simply captured by those with more effective and far-reaching connections. The .findings reveal the dynamics of how the poor both disengage from and are isolated by and from the non-poor. They further describe how the social networks of poor and non-poor households have polarized and separated in a process that parallels the sharp socioeconomic stratification that has taken place since national independence in 1991. The study examines not only how the networks have separated, but also how each has changed in character.